Stability and frequency compensation techniques for low-power operational amplifier design - Huỳnh Công Tú; Nguyễn Văn Hào; Huỳnh Nguyễn Bảo Phương (My University, 2022)
Stability and frequency compensation techniques for low-power operational amplifier design
Keywords: Bộ khuếch đại thuật toán; Bù tần số; Thiết kế công suất thấp